2020
DOI: 10.3389/fmicb.2020.575828
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mycobacterial MSMEG-3762/63 Efflux Pump in Mycobacterium smegmatis Drug Efflux

Abstract: Multi-drug resistant tuberculosis (MDR-TB) represents a major health problem worldwide. Drug efflux and the activity of efflux transporters likely play important roles in the development of drug-tolerant and drug-resistant mycobacterial phenotypes. This study is focused on the action of a mycobacterial efflux pump as a mechanism of drug resistance. Previous studies demonstrated up-regulation of the TetR-like transcriptional regulator MSMEG_3765 in Mycobacterium smegmatis and its ortholog Rv1685c in Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Such other efflux pumps could be, for example, the homologs of Mycobacterium tuberculosis Rv1145, Rv1146, Rv1877, Rv2846c ( efpA ), and Rv3065 ( mmr and emrE ) [ 4 ]. In the study by De Siena et al [ 33 ], two other ortholog operons, Rv1687/86/85c in M. tuberculosis and MSMEG_3762/63/65 in M. smegmatis , both designated as ABC efflux pump systems, were identified, sharing a high percentage of identity. It was shown that the protein complex MSMEG-3762/63, annotated as an efflux pump, is involved in the resistance toward first- and second-line anti-TB drugs, such as rifampicin and ciprofloxacin, as well as in the formation of mycobacterial biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such other efflux pumps could be, for example, the homologs of Mycobacterium tuberculosis Rv1145, Rv1146, Rv1877, Rv2846c ( efpA ), and Rv3065 ( mmr and emrE ) [ 4 ]. In the study by De Siena et al [ 33 ], two other ortholog operons, Rv1687/86/85c in M. tuberculosis and MSMEG_3762/63/65 in M. smegmatis , both designated as ABC efflux pump systems, were identified, sharing a high percentage of identity. It was shown that the protein complex MSMEG-3762/63, annotated as an efflux pump, is involved in the resistance toward first- and second-line anti-TB drugs, such as rifampicin and ciprofloxacin, as well as in the formation of mycobacterial biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…There has been much research performed on genes involved in the intrinsic and acquired antimicrobial drug resistance of mycobacteria, including MDR/XDR M. tuberculosis. Besides the role of efflux pumps in antibiotic resistance, they might also be involved in bacterial behaviors associated with virulence, biofilm development, and quorum sensing-dependent expression of virulence factors [ 33 , 37 , 38 ]. Based on the findings of this study, the interplay of 4 and 6 in P. ostruthium fractions seems to be crucial for efflux pump inhibitory-, antibacterial, and resistance-modulatory effects of this plant.…”
Section: Discussionmentioning
confidence: 99%
“…coli strains and 200 µl per well for M. smegmatis strains [27]. Two-fold serial dilutions of different antibiotics were made in cation-adjusted MH broth and 7H9 media and each well was inoculated with 10 5 cells.…”
Section: Methodsmentioning
confidence: 99%
“…MICs of different compounds were determined using micro-broth dilution method and assessed according to Clinical and Laboratory Standards Institute (CLSI) guidelines [26]. The assays were performed in 96-well micro-titre plates with an assay volume of 300 µl per well for E. coli strains and 200 µl per well for M. smegmatis strains [27]. Two-fold serial dilutions of different antibiotics were made in cation-adjusted MH broth and 7H9 media and each well was inoculated with 10 5 cells.…”
Section: Determination Of Susceptibility Towards Antibiotics and Meta...mentioning
confidence: 99%
“…We have previously characterized the ABC-type MSMEG-3762/63 e ux pump in Mycobacterium smegmatis, a mycobacterium widely used as a model system for M. tuberculosis physiology [17,18]. This e ux pump shares a high percentage identity with the M. tuberculosis Rv1687/86c pump [19,20]. In our previous studies, we demonstrated that the TetR-like MSMEG-3765 repressor was able to negatively regulate the expression of the MSMEG_3762/63/65 operon and of the homologous Rv1687/86/85c operon, encoding the e ux pump and its regulator Rv1685c in M. tuberculosis [19].…”
Section: Introductionmentioning
confidence: 99%